A relação da comunicação entre as pessoas em papel de gestão em equipes locais e geograficamente dispersas de projetos - Calheira, Elida Cristina Dias (2023)
Within organizations, communication aims to transmit relevant information in a secure manner, through communications and instructions, monitoring of work and delegation of tasks. Despite this, in a project context, team members are often unable to communicate and share knowledge effectively, and such tasks are the responsibility of the person in the management role, which aims, in a way, to maintain regular communication between all stakeholders. In this way, people in a project management role contribute to the expectations of stakeholders being understood, met, and shared as a whole. Thus, some elements can influence the aspect of an organization's communication that can occur, which can cause positive and/or negative effects on project teams. As a highlight of this relationship, the communication between the people in the management role and the project team occurs due to the competence of each individual, who employ some procedures to maintain good communication with the team members. During this process, both people in management roles and individuals on a project team face certain barriers, and to minimize this scenario, they can use certain methods so that project teams, both local and geographically dispersed, can communicate in the best possible way throughout the project lifecycle. In this context, the aim of this dissertation was to describe the relationship of communication between people in management roles and the local and geographically dispersed project team. To achieve the objective, this research was developed in two phases. In the first phase, a systematic review of the literature was carried out with a research corpus with 122 articles, where it was possible to identify how communication occurs in a project environment. As a result, four categories were identified that contribute to the communication relationship between people in management roles and the project team: Competencies for communication in a project environment, Communication Strategies, Communication in geographically dispersed teams and Communication Barriers. In view of these categories, it was possible to present the associated factors of the relationship and the respective impacts on organizations. In the second phase, field research was carried out with semi-structured interviews to validate factors associated with the relationship of communication between people in management roles and the project team and the respective impacts on organizations. Thus, based on the results and information from the mapped experiences of the interviewees, it was intended to analyze the relationship of communication between people in management roles and the project team, both from local and geographically dispersed teams. In relation to practical contributions, we highlight the significant variations in the way communication occurs between people in management roles and project teams according to the context in which it is inserted. In terms of theoretical contributions, the results obtained from the systematic literature review compared with empirical research will allow the discussions on the communication phenomenon and the project team to advance. This research is aligned with research line 2 "Project Management", linked to the Graduate Program in Project Management – PPGP UNINOVE. This dissertation is also aligned with other research of his advisor linked to the axis project "Agile and Hybrid Projects".